Evaluation of the Implementation of the Early Childhood Feeding Program at Natur Islam Kindergarten, Bekasi CIPP Method (Early Childhood Education & Parenting (ECEPA), 2025)
This study aims to evaluate the context, inputs, processes, and results of the lunch program at Natur Islam Kindergarten. This research is a type of research evaluation with a descriptive qualitative approach. The evaluation model used in this study is CIPP (Context, Input, Process, Product) developed by Stufflebeam. Data was collected through interviews, observation, and documentation. Data analysis is carried out by reducing data, then presented in the form of descriptions, and verified by drawing conclusions.The results showed that the evaluation of the context of the healthy feeding program showed that the program had clear objectives and planning. Evaluation of lunch program inputs shows that the school plays a good role in running this program. Evaluation of the lunch program process shows that the implementation of this program is in accordance with the daily nutritional needs of children based on balanced nutrition guidelines and the contents of my plate. However, the obstacle faced is the lack of cooperation of parents in providing food in accordance with balanced nutrition guidelines and the contents of my plate to children at home. Evaluation of program results showed that children achieved their target weight according to their age, and none of the children experienced malnutrition or stunting.
Keywords: Parental perception; Academic stress; Early childhood